CHOP-treated Mammary Non-hodgkin's Malignant Lymphoma in a Female Patient with HIV + On Retroviral Treatment - Case Report - Bakraoui, K. El; Ghissassi, I. El; Boutayeb, S.; Mrabet, H.; Errihani, H. (International Journal of Innovative Research in Medical Science, 2019)
HIV infection greatly increases the risk of developing lymphoma. NHL is present in approximately 3% of the HIV-positive population at the time of their HIV diagnosis. Twenty percent of HIV-positive patients develop NHL. Risk factors for an association of the NHL with HIV include: low CD4 T cell count, high viral load, age, and male. We report the case of a 35-year-old mother of three children having a history of the death of the husband following the neurological complications of AIDS, the patient was subsequently diagnosed with HIV + and then placed on retroviral treatment. After 6 months the patient reported a breast swelling with pelvic pain, a breast biopsy performed showing a large B-cell NHL. The extension assessment reveals localizations: mammary, bilateral ovarian and adrenal right of a lymphomatous process, the BOM is normal and the CD4 rate is 517 / mm3. CHOP-type systemic chemotherapy with intrathecal chemotherapy has been initiated. The post-treatment evaluation was in favor of a complete clinical and radiological response. The prognosis of patients with AIDS-related lymphoma is associated with the stage of the disease, extraganglionic involvement including bone marrow, CD4 cell count, and performance status. Median survival varies from 8 to 20 months, which remains much lower than that of non-HIV-associated lymphomas.